IMPLEMENTASI KEBIJAKAN PENGANGKATAN TENAGA HONORER - Ningriani, Ocza; Yuliani, Febri; Ruzikna, Ruzikna (Jurnal Ilmu Administrasi Negara, 2018)
Implementation of Honorary Appointment Policies. This study aims to determine and analyze the implementation of policy Regulation No. 48 of 2005 on the appointment of honorary staff. The method used in this research is qualitative research method. Sources of data were taken from several people related to the research, among others: honorary employees who were appointed in 2005 in Dumai City and Head of Dumai City BKD. Technique of collecting data using interview technique, observation, while technique of data analysis by using qualitative technique with descriptive approach. Based on the results of research known that Impelemtasi policy of appointment of honor teachers become CPNS is still not optimal. Factors that hinder it are still low objectivity, transparency / openness of government in implementing the policy.